Penyuluhan Perilaku Menstrual Hygiene Pada Remaja Putri Kelas VII di SMP N 1 Sungai Tebelian Tahun 2025 - Atri Rudtitasari; Khairulisni Saniati; Asri Fitri Yati; Dian Ika Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2025)
In Indonesia, the prevalence of genital infections due to poor genital hygiene is estimated to reach 90–100 cases per 100,000 population per year. Globally, approximately 75% of women have experienced vaginal discharge at least once in their lifetime, 45% of them have experienced it more than once, and approximately 25% of women in Europe have experienced vaginal discharge. In Indonesia, 75% of women have experienced vaginal discharge at least once, and 45% have experienced it more than once. This condition shows the importance of education about reproductive organ hygiene, especially for adolescent girls who are experiencing puberty. This community service activity aims to increase the knowledge of female students of SMPN 1 Sungai Tebelian about menstrual hygiene behavior through structured counseling. The activity implementation method includes four stages, namely (1) initial survey, (2) approach to the school, (3) activity socialization, and (4) presentation of counseling materials. Knowledge measurement was carried out before and after the activity using a questionnaire, then analyzed using a Paired Sample Test. The results showed that before the counseling, all respondents (37 female students) were in the sufficient knowledge category (100%). After the counseling and post-test, all respondents experienced an increase in knowledge so that they were in the good category (100%). The results of the Paired Sample Test analysis showed a Sig. (2-tailed) value of 0.000 (<0.05), which indicated a significant difference between the pre-test and post-test scores. The conclusion of this activity is that health counseling has a positive and significant influence on increasing female students' knowledge about menstrual hygiene behavior. Education that is carried out interactively and adapted to the characteristics of adolescents has proven effective in encouraging better understanding, so it is hoped that it can prevent reproductive health problems in adolescent girls in the future.